Strengthening Concurrent Enrollment Through NACEP Accreditation. Issue 169 (March 2015) - Scheffel, Kent; McLemore, Yvette; Lowe, Adam; Taylor, Jason L.; Pretlow, Joshua
<x xml:space="preserve">Abstract</x> This chapter describes how implementing the National Alliance of Concurrent Enrollment Partnerships' 17 accreditation standards strengthens a concurrent enrollment program, enhances secondary–postsecondary relations, and benefits students, their families, and secondary and postsecondary institutions.